(untitled) (Scientific journal of the Fergana State University, 2024)
Since the second half of the 20th century, threats to national identity, national self-awareness, national culture and values began to increase, while the rapid growth of the national paradigm has been observed throughout the world. The concepts of democracy and universal values, which from the very beginning were considered the most unique values ​​of humanity, are transformed into the form of threats and become powerful weapons for manipulating public consciousness. The article makes an attempt to reveal the significance of mahalla as a means of preserving, forming and transmitting from generation to generation the values ​​of national identity and as a protective factor against threats to national identity.